2000
DOI: 10.1097/00002826-200001000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinesia in Huntington's Disease

Abstract: Huntington's disease (HD) is characterized by the presence of hyperkinesias, but bradykinesia is also present in most patients. We studied the motor performance of 18 patients with genetically proven HD (age, 38.5 +/- 10 y; clinical stage, 1.7 +/- 1.7; (CAG) triplet length, 49.2 +/- 6.8 triplets; all but three patients were free from neuroleptics) and compared with a control group (n = 18) and with a typical Parkinson's disease (PD) group (n = 20). Motor study included the four timed tests commonly used for PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Although HD is classically defined as a hyperkinetic syndrome [1][2][3][4][5][6], bradykinesia is usually present as well [2][3][4][5][6][7][8][9][10][11][12]. Bradykinesia is not restricted to patients with early onset HD; patients with the classic form also develop bradykinesia with the progression of the disease [4,8,12]; in addition, a strong correlation between decreased motor activity and functional disability has been found [4,8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HD is classically defined as a hyperkinetic syndrome [1][2][3][4][5][6], bradykinesia is usually present as well [2][3][4][5][6][7][8][9][10][11][12]. Bradykinesia is not restricted to patients with early onset HD; patients with the classic form also develop bradykinesia with the progression of the disease [4,8,12]; in addition, a strong correlation between decreased motor activity and functional disability has been found [4,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Bradykinesia in HD has been studied by different methods [2][3][4][5][6][7][8][9][10].We previously used the four timed tests (CAPIT) currently used in Parkinson's disease (PD) [13]; not only were HD patients slower than controls, but also when compared with a typical PD group [12].…”
Section: Introductionmentioning
confidence: 99%
“…Timed tests included right and left alternating pronation-supination (PS), finger tapping (FT), and movement between two points (MTP), and walking test (WT). Timed tests are commonly used for evaluation of bradykinesia in patients with PD [37], have shown a good correlation with bradykinesia and functional impairment in Parkinson's [38], and in Huntington's diseases [39], and have been used to study the physiological decline of motor performance with aging in normal subjects [8]. However, reference values at different ages and gender are not well established, and a recently published study assessing MTP and WT in 138 PD patients and 157 controls, showed that, despite PD patients were slower than control, only 17% of PD patients were slower than the "normal range" of controls.…”
Section: Evaluation Of Motor Performancementioning
confidence: 99%
“…Evaluation included four timed tests (right and left pronation–supination, finger-tapping, movement between two points, and walking test) and three computer-based tests. The timed tests used correlate with bradykinesia and functional impairment in PD71 and Huntington's disease72 and have been used to study age-related motor performance decline in normal subjects 73, 74. Tests performed on a personal computer included repetitive key pressing speed (frequency), visual reaction time, and movement time, which were all performed with both upper extremities.…”
Section: Slowed Movements In Essential Tremormentioning
confidence: 99%